Decision-making in information seeking on texts: an eye-fixation-related potentials investigation - FREY, Aline; IONESCU, Gelu; LEMAIRE, Benoit; LÓPEZ-OROZCO, Francisco; BACCINO, Thierry; GUÉRIN-DUGUÉ, Anne (Frontiers in Systems Neuroscience, 2013)
Reading on a web page is known to be not linear and people need to make fast decisions about whether they have to stop or not reading. In such context, reading and decision-making processes are intertwined and this experiment attempts to separate them through electrophysiological patterns provided by the Eye-Fixation-Related Potentials technique (EFRPs). We conducted an experiment in which EFRPs were recorded while participants read blocks of text that were semantically highly related, moderately related and unrelated to a given goal. Participants had to decide as fast as possible whether the text was related or not to the semantic goal given at a prior stage. Decision making (stopping information search) may occur when the paragraph is highly related to the goal (positive decision) or when it is unrelated to the goal (negative decision). EFRPs were analyzed on and around typical eye fixations: either on words belonging to the goal (target), subjected to a high rate of positive decisions, or on low frequency unrelated words (incongruent), subjected to a high rate of negative decisions. In both cases, we found EFRPs specific patterns (amplitude peaking between 51-120ms after fixation onset) spreading out on the next words following the goal word and the second fixation after an incongruent word, in parietal and occipital areas. We interpreted these results as delayed late components (P3b and N400), reflecting the decision to stop information searching. Indeed, we show a clear spill-over effect showing that the effect on word N spread out on word N+1 and N+2.